Coatomer, but not P200/myosin II, is required for the in vitro formation of trans-Golgi network-derived vesicles containing the envelope glycoprotein of vesicular stomatitis virus - Simon, Jean-Pierre (The National Academy of Sciences, 1998)
Using a cytosol and nucleotide dependent assay that we previously developed, we have investigated the requirement for coat proteins in the in vitro production of trans-Golgi network (TGN)-derived vesicles from a Madin-Darby canine kidney (MDCK) cell Golgi fraction that contains the (35)S-labeled, terminally glycosylated, envelope glycoprotein of vesicular stomatitis virus (VSV-G) accumulated in the TGN. We found that the TGN-derived vesicles, like those involved in intra-Golgi transport and in retrograde transport to the endoplasmic reticulum, contain a coatomer coat and that coatomer is required for their formation. Thus, after they are produced with GTPγS, the coated vesicles could be captured on beads containing anticoatomer antibody. Moreover, a cytosolic protein fraction depleted of coatomer could not support vesicle formation but it did so after purified coatomer was added. We also determined that P200/myosin II does not play an essential role in the in vitro generation of TGN-derived vesicles. Thus, removal of this protein from the cytosol, by differential salt precipitation or binding to phalloidin-induced actin filaments, had no effect on vesicle generation. Nevertheless, immunodepletion of cytosol using the anti-P200/myosin II AD7 antibody abolished vesicle generation and that antibody was capable of effectively immunocapturing coated vesicles, even when these were generated in the absence of P200/myosin II. These effects, however, are explained by the unexpected finding that the AD7 antibody interacts with undenatured coatomer.